IMPLEMENTASI PROGRAM LITERASI DALAM MENGEMBANGKAN KECERDASAN VERBAL-LINGUISTIK SISWA DI SEKOLAH DASAR SWASTA KUPU-KUPU - Rasendriya Kirei Thania; Mohamad Syarif Sumantri; Otib Satibi Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: 1) Describe the implementation of the literacy program at SDS Kupu-Kupu, 2) Explain the role of the literacy program in developing the verbal-linguistic intelligence of fifth-grade students, and 3) describe the impact of the literacy program on the non-academic achievements of fifth-grade students in areas related to language skills. This research uses a qualitative approach with a case study method, involving the principal, teachers, library staff, and fifth-grade students at SDS Kupu-Kupu as research subjects. Data analysis was conducted using the Miles and Huberman qualitative data analysis model, which includes three stages: data reduction, data display, and conclusion verification. The results of the study show that the implementation of the literacy program at SDS Kupu-Kupu was carried out in stages through the habituation, development, and learning phases. The program contributed positively to the development of students verbal-linguistic intelligence, such as listening, speaking, reading, and writing evident in their reading habits, creative writing, and confidence in expressing opinions and participating in discussions. Additionally, the program had a positive impact on students non-academic achievements in language-related areas, supported by the school’s encouragement for student participation in language competitions, which helped build self-confidence and nurture students’ interests and talents.